Deterministic and Stochastic Holling-Tanner Prey-Predator Models - Thapa, Bharat Bahadur; Shrestha, Samir; Gurung, Dil Bahadur (Advances in Engineering and Technology: An International Journal, 2021)
A modified version of the so called Holling-Tanner prey-predator models with prey dependent functional response is introduced. We improved some new results on Holling-Tanner model from Lotka-Volterra model on real ecological systems and studied the stability of this model in the deterministic and stochastic environments. The study was focused on three types of stability, namely, stable node, spiral node, and center. The numerical schemes are employed to get the approximated solutions of the differential equations. We have used Euler scheme to solve the deterministic prey-predator model and we used Euler-Maruyama scheme to solve stochastic prey-predator model.